Effect of binge eating disorder on the outcomes of laparoscopic gastric bypass in the treatment of morbid obesity - Eduardo García Díaz; María Elena Jerez Arzola; Tomás Martín Folgueras; Luis Morcillo Herrera; Alejandro Jiménez Sosa (Nutrición Hospitalaria, 2013)
Introduction: Previous studies about the effect of binge eating disorder (BED) on the outcomes of laparoscopic gastric bypass (LGBP) are controversial. These studies have not compared patients with and without BED according to the Bariatric Analysis and Reporting Outcome System (BAROS), which takes into account weight loss, correction of comorbidities, improvement in quality of life and complications. Objectives: To assess whether BED predicts worse outcomes after LGBP, according to BAROS parameters. Methods: We carried out a cohort study which included 45 morbidly obese patients operated with LGBP. Patients with preoperative BED were identified by Questionnaire on Eating and Weight Patterns-Revised and results were evaluated by BAROS system. Results: Prevalence of BED was 21.4%. Median postoperative follow-up was 12 months. BED patients experienced after LGBP lower rates of resolution of hypertension (42.9% vs. 92.9%; p = 0.025) and were complicated by stenosis of the gastrojejunal anastomosis more frequently (70% vs. 17.1%; p = 0.003) than patients without binge eating. No differences in BAROS score, percentage of excess weight loss and quality of life were found. Conclusions: BED patients experienced after LGBP lower rates of resolution of hypertension and higher rates of anastomotic stenosis. BAROS score, weight loss and quality of life are comparable to that of patients without.